Mission statement crafted by the National Annual Corporate Report Awards (NACRA) winners - Ayoup, Hazeline; Hamdan, Mohd Diah; Marimuthu, Munusamy (Universiti Utara Malaysia, 2004)
This study focus on Malaysian public listed companies which have receive NACRA corporate report award since it was introduced. It tries to view the enforcement by NACRA pertaining to the disclosure of mission statement by companies in their annual report. It is shown by based on the number of mission statement produce by companies in terms of its components. Result reveals that, only few of the NACRA award winners concern about disclosing its mission statement in their annual report before 1990. However the number of companies disclosing their mission statement in the annual report increased gradually from 1990 until 2002. However, result also reveals that there are winners which never disclosed its mission statement even once in their annual report. The study also found that for companies which disclosed their mission statement, the rank of key companies which disclosed their mission statement, the rank of key component of the mission by degree of importance is consistent with the rank addressed in the previous literature. Finally, it was found that since NACRA was introduced, besides increasing number of mission statement disclosed in the annual report, companies are also trying to develop a comprehensive mission statement which can be seen by the increased in number of key components covered in their mission statement.